Hubungan Antara Kontrol Diri dengan Gaya Hidup Hedonis pada Mahasiswa di Kota Medan - Rotua Kristanti Sinurat; Karina Meriem Beru Brahmana (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The hedonistic lifestyle has become a growing phenomenon among college students and is characterized by a tendency to pursue pleasure, excessive consumption, and an orientation towards social prestige. This study aims to determine the relationship between self-control and a hedonistic lifestyle among college students in Medan City. The study used a quantitative approach with a correlational design. The subjects were active college students in Medan City selected using a purposive sampling technique, with a total of 400 respondents. Data collection was carried out through a digital questionnaire using the Self-Control Scale (27 valid items; α = 0.906) based on Averill's theory and the Hedonic Lifestyle Scale (13 valid items; α = 0.924) based on Kotler and Armstrong's theory. Data analysis was performed using Spearman's Rank correlation. The results showed that the level of self-control of college students was in the high category with an empirical average value of 64.53, while the hedonic lifestyle was in the low category with an empirical average value of 31.38. The results of the correlation test showed a significant negative relationship between self-control and a hedonic lifestyle. This means that the higher a student's ability to control their thoughts, emotions, and behavior, the lower their tendency to adopt a hedonistic lifestyle. This finding demonstrates the importance of strengthening self-control as a preventative measure against the consumerist influences of the social environment and digital media